Drying of Lithium‐Ion Battery Anodes for Use in High‐Energy Cells: Influence of Electrode Thickness on Drying Time, Adhesion, and Crack Formation. Issue 11 (25th September 2019) - Kumberg, Jana; Müller, Marcus; Diehm, Ralf; Spiegel, Sandro; Wachsmann, Christian; Bauer, Werner; Scharfer, Philip; Schabel, Wilhelm
Abstract : When fabricating battery electrodes, their properties are strongly determined by the adjusted drying parameters. This does not only affect their microstructure in terms of adhesion, but also influences cell performance. The reason is found to be the binder transported to the surface during drying. Herein, it is shown that when thicker electrodes are processed, new challenges arise. On the one hand, loss of adhesion associated with certain drying conditions becomes a more serious problem; on the other hand, cracking occurs at a certain drying rate and with increasing electrode thickness. Abstract : The drying process of electrodes for lithium‐ion batteries of different thicknesses is investigated. The dependency of adhesion, crack formation, and drying kinetics on drying conditions is shown and limiting factors are proposed. Increased drying rates and area loadings lead to an adhesion loss which can be compensated by different processing routes to some extent as presented here.